Overview of migraine care, impact of the disease, and patient experience in France through patient voices: a cross-sectional and participatory survey study - Anne Duburcq; Manon Molins; Sabine Debremaeker; Julie Joie; Luna Lopes; Camille Nevoret; Olivia Begasse de Dhaem (The Journal of Headache and Pain)
Abstract Background This study aims to improve the understanding of the patient journey via the perspectives of patients with migraine. Methods The questionnaire was created by patients. It was based on the experiences of 24 patients with migraine and 4 members of the patient advocacy organization La Voix des Migraineux. Two focus groups were held to assess the various dimensions of the patient journey. This survey was accessible on the MoiPatient online platform between March 19th and May 17th, 2022. Results Out of the 683 participants (average age: 41.8 years; female: 92.4%; average age at first migraine attack: 16.2 years), 95.9% had received a formal migraine diagnosis from a physician. Migraine had a significant impact on most participants (96.0% had a severe HIT-6 score and 70.7% had severe disability on the MIDAS). Unmet patients’ needs highlighted in this study included diagnosis delay (mean 7.5 years), treatment delay, limited access to neurologists and/or headache specialists, long trial-and-error process of different medications (participants had tried an average of 5.6 acute treatments and 5.0 preventive treatments), numerous (7.2 side effects per participants on average) and often inadequately addressed side effects, suboptimal patient education, and the need for a therapeutic, empathic, and supportive relationship between patients and healthcare professionals. Participants had a negative perception of the care journey and experience with healthcare professionals: 36.2% described their care journey as an uphill battle (“parcours du combatant”). More than half of patients did not feel heard nor supported by healthcare professionals. Conclusion Patients with migraine have to face a multitude of complex obstacles trying to get the care they deserve. The burden of disease is amplified by the complexity of the migraine patient’s journey, both in terms of diagnosis and treatment. This study highlights specific areas in need for improvement.